Zimbabwe Stock Exchange and efficiency in the multiple currency exchange rate regime - Chikoko, Laurine; Muparuri, William (Academia Publishing, 2016)
In this paper, the Zimbabwe Stock Exchange (ZSE) was tested to see whether it is efficient or not after the country adopted the multiple currency exchange rate regime. To achieve this, the weak form market efficiency was tested. Data on daily and weekly closing stock prices over a period of 19 February 2009 to 31 December 2012 was used. The non-parametric and parametric research methods through the partial autocorrelation function were used. The results of both tests showed that the successive stock price changes were dependent which indicates that the ZSE was not efficient in the weak form when the country used multiple currencies. In addition, the results showed evidence of autocorrelation which implies that during the period under study, the ZSE did not follow random walk hypothesis. In order to make the ZSE efficient we recommend that regulators may consider putting in place measures and regulations that enable large number of well informed investors. The ZSE may insist on timely release of correct and quality information to boost public and investor confidence and provide a platform for informed decision making by the investing public. There may be need for the removal of fees and other costs by the ZSE committee which hinder smooth trading on the stock exchange. Where removal is not feasible, such costs must be kept to the minimal to avoid hindrance on efficiency.